Recent Advances in the Recognition Elements of Sensors to Detect Pyrethroids in Food: A Review - Le Zhang; Mingqi Zhao; Ming Xiao; Moo-Hyeog Im; A. M. Abd El-Aty; Hua Shao; Yongxin She (Biosensors, 2022)
The presence of pyrethroids in food and the environment due to their excessive use and extensive application in the agriculture industry represents a significant threat to public health. Therefore, the determination of the presence of pyrethroids in foods by simple, rapid, and sensitive methods is warranted. Herein, recognition methods for pyrethroids based on electrochemical and optical biosensors from the last five years are reviewed, including surface-enhanced Raman scattering (SERS), surface plasmon resonance (SPR), chemiluminescence, biochemical, fluorescence, and colorimetric methods. In addition, recognition elements used for pyrethroid detection, including enzymes, antigens/antibodies, aptamers, and molecular-imprinted polymers, are classified and discussed based on the bioreceptor types. The current research status, the advantages and disadvantages of existing methods, and future development trends are discussed. The research progress of rapid pyrethroid detection in our laboratory is also presented.